Perkembangan Isu Perempuan dalam Novel Andina Dwifatma: Develompment of Women’s Issues in Andina Dwifatma’s Novels - Dewi, Liana Shinta; Daniel Fahmi Rizal, Muhammad (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
Violence against women in Indonesia remains widespread, with limited awareness. Literature, particularly Andina Dwifatma’s novels Semusim dan Semusim Lagi (SSL) and Lebih Senyap dari Bisikan (LSB), can effectively address this issue. This research aims to identify emerging women's issues in these works, using feminist theory for analysis. The study used note-taking for data collection and content analysis for evaluation. Findings reveal themes of power dynamics, subordination, stereotyping, and various forms of violence, including verbal abuse, physical aggression, psychological neglect, and sexual grooming, often perpetuated by those who uphold patriarchal values. Women lacking agency struggle to resist this violence. SSL primarily examines violence through themes of fatherlessness and grooming, with characters who typically lack the ability to resist. In contrast, LSB explores the complexities of domestic life and women's burdens, featuring characters with greater agency to confront their challenges.